Beauvallet [compact disc, unabridged] - Heyer, Georgette, 1902-1974 (Brilliance Audiobooks, 2015)
Mad Nicholas to his friends, Scourge of Spain to the enemy, Sir Nicholas Baeuvallet has never been known to resist a challenge. When a captured galleon yields the lovely Dona Dominica de Rada y Sylva, he vows to return her and her father to the shores of Spain. But he has no sooner done so than he proposes a venture more reckless than any of his exploits on the high seas.